The Effect of Cost Accounting Information Systems on Operational Cost Control: Study at A Consulting Company in The City of Bandung - Neulis Yeni; Anton Tirta Komara; Boy Suzanto; Jimmy Rusjiana (Acman: Accounting and Management Journal, 2023)
The purpose of this study was to determine the Operational Cost Accounting Information System on Internal Control of Operating Costs and how much influence the Operational Cost Accounting Information System has on Internal Control of Operational Costs at a consulting firm in Bandung. The research method used is descriptive analysis, while the data collection technique is by distributing questionnaires to 30 respondents. This study uses the Pearson Moment correlation data analysis technique and the coefficient of determination analysis technique using Excel and SPSS 25 For Windows Software in its operations. The regression equation research results show the positive influence of the Operational Cost Accounting Information System on the Internal Control of Operational Costs. This study obtained the results from the regression analysis, namely Y = a + bX Y = 16.888 + 0.567X, which means that if the value of X = 0, then Y = 16.888. So if X changes one unit, it will affect Y by 0.567. Therefore, the Operational Cost, Accounting Information System, influences the Internal Control of Operational Costs by 35.9%, while other factors affect as much as the remaining 64.1%. Thus, the researchers concluded that the Operational Cost accounting information system influenced the Internal Control of Operational Costs Case Study at a Consulting Firm in Bandung City.